A study of the genus Fagineura (Hymenoptera, Tenthredinidae, Nematinae) - Hara, Hideho; Ibuki, Shinichi (Zootaxa, 2022)
The East Asian genus Fagineura Vikberg & Zinovjev, 2000 (Hymenoptera, Tenthredinidae) is redefined to comprise the following 11 species, divided into two species groups: F. crenativora species group: F. brevicornis Liu, Li & Wei, 2021 from China, F. crenativora Vikberg & Zinovjev, 2000 from Japan, F. flactoserrula Liu, Li & Wei, 2019 from China, F. longitangia Liu, Li & Wei, 2021 from China, F. parva Hara, sp. nov. from Japan, F. xanthosoma Liu, Li & Wei, 2019 from China; F. quercivora species group: F. flavomaculata Hara, sp. nov. from Japan and Korea, F. fulvistriata Hara, sp. nov. from Japan, F. glabella Hara, sp. nov. from Japan and Korea, F. quercivora (Togashi, 1997), comb. nov. [= Dineura quercivora Togashi, 1997] from Japan and Korea, F. togashii Hara, nom. nov. [replacement name for F. quercivora Togashi, 2006; junior secondary homonym of F. quercivora (Togashi, 1997)] from Japan and Korea. A key to these 11 species is given. Descriptions or additional descriptions are given for the species from Japan and Korea. Fagineura quercivora and F. togashii are recorded from Korea for the first time. For F. flavomaculata, F. fulvistriata, F. glabella, F. quercivora and F. togashii, information on the immature stages, host plants and life history is provided.